Brenner & Rector's the kidney - Taal, Maarten W.; Brenner, Barry M., 1937-; Rector, Floyd C. (Elsevier/Saunders, 2012)
Includes sections on Global Considerations in Nephrology and Pediatric Nephrology, as well as chapters on clinical trials, cardiovascular and renal risk prediction in chronic kidney disease, identification of genetic causes of kidney disease, and others.